2006
DOI: 10.1159/000095040
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antibacterial Activity of a Special Silk Textile in the Treatment of Atopic Dermatitis

Abstract: Background: Increased skin Staphylococcus aureus colonization is frequently found in atopic patients. The reduction of local overinfection decreases skin inflammation and improves the flares. Objective: To evaluate the effectiveness of the antimicrobial activity of a silk fabric (MICROAIR DermaSilk®) coated with alkoxysilane quaternary ammonium with durable antimicrobial properties (AEGIS AEM 5572/5) in children affected by atopic dermatitis (AD). Methods: Sixteen children, 12 affected by AD with symmetric ecz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 25 publications
1
50
0
Order By: Relevance
“…A significant reduction of the mean local SCORAD index of the DermaSilk-covered arm was observed in comparison with cotton- and AEGIS-free-silk-covered arms. Although AEGIS AEM 5772/5 has antibacterial properties in vitro [10], recent studies performed by Ricci et al [15, 16 ]were unable to demonstrate antimicrobial activity in vivo, though demonstrating superior efficacy in AD compared with cotton. Ricci et al [15] considered a quantitative microbiological improvement significant if the number of colony-forming units of S. aureus per square centimetre was reduced at least to half of the baseline value; they observed a reduction of S. aureus colonies, but it was not significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant reduction of the mean local SCORAD index of the DermaSilk-covered arm was observed in comparison with cotton- and AEGIS-free-silk-covered arms. Although AEGIS AEM 5772/5 has antibacterial properties in vitro [10], recent studies performed by Ricci et al [15, 16 ]were unable to demonstrate antimicrobial activity in vivo, though demonstrating superior efficacy in AD compared with cotton. Ricci et al [15] considered a quantitative microbiological improvement significant if the number of colony-forming units of S. aureus per square centimetre was reduced at least to half of the baseline value; they observed a reduction of S. aureus colonies, but it was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Although AEGIS AEM 5772/5 has antibacterial properties in vitro [10], recent studies performed by Ricci et al [15, 16 ]were unable to demonstrate antimicrobial activity in vivo, though demonstrating superior efficacy in AD compared with cotton. Ricci et al [15] considered a quantitative microbiological improvement significant if the number of colony-forming units of S. aureus per square centimetre was reduced at least to half of the baseline value; they observed a reduction of S. aureus colonies, but it was not significant. They suggested that the lack of efficacy in vivo was due to the strong adhesion of AEGIS AEM 5572/5 to the fibres preventing in this way its penetration into the skin and sufficient contact with bacteria to kill them.…”
Section: Discussionmentioning
confidence: 99%
“…Although wearing clothing to protect one's skin is not a new practice, there are limited investigations on physiological responses, such as stratum corneum hydration, TEWL, sweat loss, surface ion concentration or antimicrobial properties when the skin gets in contact with a fabric [1][2][3][9][10][11] .…”
Section: Discussionmentioning
confidence: 99%
“…The skin of patients with AD is often colonized with Staphylococcus aureus and the quantity of S. aureus correlates with eczema severity [2,3,4,5,6,7]. Consequently, several studies demonstrated that reduction of S. aureus either by antibiotics, antiseptics or by anti-inflammatory treatment (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Such a commercially available fabric (DermaSilk®) has antibacterial properties thanks to treatment with AEGIS AEM 5772/5, a covalently linked water-resistant antimicrobial finish for textiles based on the compound alkoxysilane quaternary ammonium [17]. In a recent trial, patients wearing DermaSilk showed significant clinical improvement of AD when compared to patients wearing cotton clothes [5, 18]. The aim of our study was to compare the effectiveness of DermaSilk with that of standard care consisting of the application of a modern topical corticosteroid and the wearing of cotton clothes in children suffering from moderate AD.…”
Section: Introductionmentioning
confidence: 99%